The Structure Of The Rat Thymus During Late Postnatal Ontogenesis And Its Changes When Exposed To An Energy Drink - Ilyasov А.S; Rakhmanova K.E (Zien Journals, 2024)
This article presents data on the structure of the thymus capsule and its trabeculae in the 1,3,6- month period of white laboratory rats. The best results were obtained by combining protocols such as staining with the van Ginzon technique for the detection of collagen fibers and histochemical staining with toluidine blue for the detection of mast cells. The article presents data from the new literature on the structure of the thymus, its cellular composition and the surrounding capsule of this organ and its changes under the energy drink influence
Keywords: Rats; Thymus; Energy Drinks